2015
DOI: 10.1021/acsnano.5b01433
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite Hydrogels: 3D Polymer–Nanoparticle Synergies for On-Demand Drug Delivery

Abstract: Considerable progress in the synthesis and technology of hydrogels makes these materials attractive structures for designing controlled-release drug delivery systems. In particular, this review highlights the latest advances in nanocomposite hydrogels as drug delivery vehicles. The inclusion/incorporation of nanoparticles in three-dimensional polymeric structures is an innovative means for obtaining multicomponent systems with diverse functionality within a hybrid hydrogel network. Nanoparticle-hydrogel combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
470
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 700 publications
(475 citation statements)
references
References 76 publications
1
470
0
4
Order By: Relevance
“…This capacity for recovery after high shear is particularly relevant for injectable gels sheared through a needle as following injection the gel would be required to revert back to its original state. Although this self-healing property has been extensively reported for polymeric systems, [13][14][15][16][17] there are fewer reports for LMW gels. [9][10][11] Pertinent examples are dipeptide gels (Fmoc-Leucinylglycine and Fmocphenylalaninylphenylalanine) which have been shown to recover after shear in similar experiments.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 98%
See 1 more Smart Citation
“…This capacity for recovery after high shear is particularly relevant for injectable gels sheared through a needle as following injection the gel would be required to revert back to its original state. Although this self-healing property has been extensively reported for polymeric systems, [13][14][15][16][17] there are fewer reports for LMW gels. [9][10][11] Pertinent examples are dipeptide gels (Fmoc-Leucinylglycine and Fmocphenylalaninylphenylalanine) which have been shown to recover after shear in similar experiments.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 98%
“…Indeed the self-healing properties of LMWGs is uncommon 12 when compared to the reported self-healing of polymer hydrogels. [13][14][15][16][17] In the studies reported here we will describe the rare self-healing properties of a nucleoside based gelator. Previously described gelation of acylated nucleoside gelators based on cytidine were carried out in a binary system of ethanol and water, where the ethanol content contributed 40 % to the overall solvent volume.…”
Section: Introductionmentioning
confidence: 99%
“…in the polymer chains, this series of hydrogels have been employed in a variety of industries, such as agriculture (water-reserving in soil and controlled release of agrochemicals), drug delivery system, separation technology, sludge/coal dewatering and so on [29,30]. Recently, the trend of research has engaged in the integration of functional nanoparticles, such as quantum dot, metal or metal oxide and carbon-based nanocomposites so as to obtain hybrid composite hydrogels with fluorescene, magnetism, dielectric and catalytic properties for a large amount of practical usages [31][32][33]. The conclusion has been drawn that the composites of hydrogels not only overwhelm the disadvantages of hydrogels by combining the advantages of constituents, but also reduce the capital of the industrial polymers.…”
Section: Palygorskite-based Composite Hydrogels For the Adsorption Ofmentioning
confidence: 99%
“…Moreover, the combination of inorganic nanoparticles with interesting physical properties can be incorporated into the nanogel network. For example, magnetic particles can be combined into a nanogel matrix forming magnetic nanogels (MNG) [28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%